Monitoring radio programs and time of day affect simulated car-driving performance. - Jäncke, Lutz; Musial, Frauke; Vogt, Joachim (Perceptual & Motor Skills)
Whether radio monitoring, task difficulty, and time of day affect driving performance was examined in a computer-controlled, simulated driving task. Driving performance was defined as the absolute deviation of the car position from road midline as displayed on the computer monitor. We found for 12 men and 8 women (i) an expected, marked deterioration of performance with increasing task difficulty, (ii) a deterioration of performance in the morning, and (iii) a deterioration of performance when subjects concurrently listened to radio programs except for the easy task conducted in the morning. The latter is supposed to be caused by a reactive increase of effort, which is induced by the concurrent radio monitoring and stimulated through a perceived impairment of attention. Reprinted by permission of the publisher, 1994.